Prolonged cenicriviroc therapy reduces hepatic fibrosis despite steatohepatitis in a diet‐induced mouse model of nonalcoholic steatohepatitis. Issue 5 (7th March 2018) - Kruger, Annie J.; Fuchs, Bryan C.; Masia, Ricard; Holmes, Jacinta A.; Salloum, Shadi; Sojoodi, Mozhdeh; Ferreira, Diego S.; Rutledge, Stephanie M.; Caravan, Peter; Alatrakchi, Nadia; Vig, Pam; Lefebvre, Eric; et al.
Abstract : Cenicriviroc (CVC) is a dual chemokine receptor 2 and 5 antagonist currently under clinical investigation for the treatment of NASH and liver fibrosis. In mouse models, CVC therapy is associated with reduced fibrosis despite ongoing steatohepatitis. Its ability to alter hepatic macrophage populations and inhibit pro‐fibrogenic gene induction in hepatic stellate cells may contribute to its observed anti‐fibrotic effect. Abstract : Nonalcoholic steatohepatitis (NASH) is a progressive liver disease projected to become the leading cause of cirrhosis and liver transplantation in the next decade. Cenicriviroc (CVC), a dual chemokine receptor 2 and 5 antagonist, prevents macrophage trafficking and is under clinical investigation for the treatment of human NASH fibrosis. We assessed the efficacy and durability of short and prolonged CVC therapy in a diet‐induced mouse model of NASH, the choline deficient, L‐amino acid‐defined, high‐fat diet (CDAHFD) model. C57BL/6 mice received 4 or 14 weeks of standard chow or the CDAHFD. CVC (10 mg/kg/day and 30 mg/kg/day for 4 weeks and 20 mg/kg/day and 30 mg/kg/day for 14 weeks) was initiated simultaneously with the CDAHFD. At 4 and 14 weeks, livers were harvested for histology and flow cytometric analyses of intrahepatic immune cells. High‐dose CVC (30 mg/kg/day) therapy in CDAHFD mice for 4 or 14 weeks inhibited intrahepatic accumulation of Ly6C high bone marrow‐derived macrophages. Prolonged CVC therapy (14 weeks) yielded no significant differences in the total intrahepatic macrophage populations among treatment groups but increased the frequency of intrahepatic anti‐inflammatory macrophages in the high‐dose CVC group. Despite ongoing steatohepatitis, there was significantly less fibrosis in CDAHFD mice receiving high‐dose CVC for 14 weeks based on histologic and molecular markers, mirroring observations in human NASH CVC trials. CVC also directly inhibited the profibrotic gene signature of transforming growth factor‐β‐stimulated primary mouse hepatic stellate cells in vitro . Conclusion: CVC is a novel therapeutic agent that is associated with reduced fibrosis despite ongoing steatohepatitis. Its ability to alter intrahepatic macrophage populations and inhibit profibrogenic genes in hepatic stellate cells in NASH livers may contribute to its observed antifibrotic effect. ( Hepatology Communications 2018;2:529‐545)